Lynch syndrome–associated urothelial carcinoma: clinical and molecular findings from a single-institution cohort - A. Rametta; M. Barella; A. Scardino; F. Barbetta; E. Tamborini; F. Perrone; A. Busico; L. Agnelli; S. Rota; E. Gusmaroli; M. Stellato; A. Nuzzo; et al. (Familial Cancer, 2026)

Progress status of the NUSES Space Mission - M. Abdullahi; R. Aloisio; S. Ashurov; U. Atalay; F.C.T. Barbato; R. Battiston; M.E. Bertaina; E. Bissaldi; D. Boncioli; L. Burmistrov; I. Cagnoli; E. Casilli; et al. (Advances in Space Research, 2026)

Effect of microbial fermentation on functional traits and volatiloma profile of pâté olive cake - Paola Foti; Cinzia L. Randazzo; Mariateresa Russo; Rosa Di Sanzo; Flora V. Romeo; Antonio Scilimati; Morena Miciaccia; Maria Grazia Perrone; Cinzia Caggia (Food Research International, 2023)

A multidisciplinary approach to estimating wolf population size for long‐term conservation - Francesca Marucco; Maria V. Boiani; Pierre Dupont; Cyril Milleret; Elisa Avanzinelli; Kristine Pilgrim; Michael K. Schwartz; Achaz von Hardenberg; Domenica Serena Perrone; Olivier P. Friard; Arianna Menzano; Francesco Bisi; et al. (Conservation Biology, 2023)
The wolf ( Canis lupus ) is among the most controversial of wildlife species. Abundance estimates are required to inform public debate and policy decisions, but obtaining them at biologically relevant scales is challenging. We developed a system for comprehensive population estimation across the Italian alpine region (100,000 km 2 ), involving 1513 trained operators representing 160 institutions. This extensive network allowed for coordinated genetic sample collection and landscape‐level spatial capture–recapture analyses that transcended administrative boundaries to produce the first estimates of key parameters for wolf population status assessment. Wolf abundance was estimated at 952 individuals (95% credible interval 816–1120) and 135 reproductive units (i.e., packs) (95% credible interval 112–165). We also estimated that mature individuals accounted for 33–45% of the entire population. The monitoring effort was spatially estimated thereby overcoming an important limitation of citizen science data. This is an important approach for promoting wolf–human coexistence based on wolf abundance monitoring and an endorsement of large‐scale harmonized conservation practices.

Integrated geophysical and geological surveys reveal new details of the large Montescaglioso (southern Italy) landslide of December 2013 - G. Calamita; M.R. Gallipoli; E. Gueguen; R. Sinisi; V. Summa; L. Vignola; T.A. Stabile; J. Bellanova; S. Piscitelli; A. Perrone (Engineering Geology, 2023)

Multimodal Neuroimaging in Schizophrenia: Description and Dissemination - C. J. Aine; H. J. Bockholt; J. R. Bustillo; J. M. Cañive; A. Caprihan; C. Gasparovic; F. M. Hanlon; J. M. Houck; R. E. Jung; J. Lauriello; J. Liu; A. R. Mayer; et al. (Neuroinformatics, 2017)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

Determination of aerosol deliquescence and crystallization relative humidity for energy saving in free-cooled data centers - L. Ferrero; L. D’Angelo; G. Rovelli; G. Sangiorgi; M. G. Perrone; M. Moscatelli; M. Casati; V. Rozzoni; E. Bolzacchini (International Journal of Environmental Science and Technology, 2015)

Prevalence of respiratory colonisations and related antibiotic resistances among paediatric tracheostomised patients of a long-term rehabilitation centre in Italy - M. Pozzi; P. Pellegrino; S. Galbiati; M. Granziera; F. Locatelli; C. Carnovale; V. Perrone; S. Antoniazzi; C. Perrotta; S. Strazzer; E. Clementi (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Epidemiological analysis on two decades of hospitalisations for meningitis in the United States - P. Pellegrino; C. Carnovale; V. Perrone; D. Salvati; M. Gentili; T. Brusadelli; S. Antoniazzi; M. Pozzi; S. Radice; E. Clementi (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Cystic fibrosis Δf508 mutation screening in Brazilian women with altered fertility - G. V. F. Brunoro; E. V. Wolfgramm; I. D. Louro; I. I. Degasperi; V. C. W. Busatto; A. M. S. Perrone; M. C. P. Batitucci (Molecular Biology Reports, 2011)

Neonatal pain analyzer: development and validation - R. Sisto; C. V. Bellieni; S. Perrone; G. Buonocore (Medical & Biological Engineering & Computing, 2006)